إصلاح المنظومة الرقابية للجان الصفقات العمومية في ظل المرسوم الرئاسي رقم 15/247 (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Administrative Control Over Public Transactions Is The Bulwark That Would Ensure The Reasonable Management Of Public Funds And Reduce The Various Forms Of Corruption That May Exist In This Field As It Is Ready For Such Thing. Public Transactions Play An Important Role In Advancing The Pace Of Development, So These Processes Usually Contain Important Financial Envelopes, That's Why The Legislator Put Them Under Different Controlling Frameworks In Order To Ensure Effectiveness In Dealing  With Public Transactions, Whether In The Case Of Internal Control Exercised By The Contracting Interest Or Those Exercised By Public Transaction Committees, Which Have Faced A Number Of Changes, In Addition To The Controlling Frameworks Introduced By The Legislator,  Enacted By Presidential Decree N° 15/247, Which We Have Highlighted Through This Study.   Keywords-  Beforehand Control, Public Transactions, Public Transaction Committees, Visa(Control), Corruption